The Study of Deep Soil Mixing for Ground Treatment in Section 1 For East Coast Rail Link (ECRL) Project During Construction Phase - Mohd Yusop, Nurzazila Humaira; Prasetijo, Joewono; Rus Azlizan bin Mohd Ali (Progress in Engineering Application and Technology, 2023)
Deep soil mixing is a ground improvement technique commonly used to address challenges associated with soft clay soil. Soft clay soil covers vast areas in many countries, making it difficult to find suitable locations for construction. This type of soil, especially when saturated with water, poses significant problems as a bearing layer for building foundations due to its susceptibility to breakage and excessive movement. Deep soil mixing has emerged as an effective method to enhance the soil surface before commencing construction activities. This study focuses on the application of deep soil mixing in the context of the East Coast Rail Link project, which involves the construction of a tunnel, subgrade, and other associated structures. Prior to implementing the deep soil mixing procedures, laboratory tests were conducted to assess the soil characteristics and determine the appropriate deep soil mixing techniques for specific soil types. The primary objectives of the design process for cement-soil columns, a key component of deep soil mixing, is to improve the qualities of local soils, such as strength and stiffness, by incorporating various cementing materials. Two approaches are commonly employed in the process of deep soil mixing which is dry method and wet method. For the construction of railway embankments in the ECRL project, the wet approach was chosen. Analysing the difference between theoretically measured coordinates and the actual coordinates obtained after implementing the deep soil mixing activity played a crucial role in this method. This study also highlights the significance of deep soil mixing in mitigating the challenges posed by soft clay soil, particularly in the construction of critical infrastructure projects like ECRL. It emphasizes the importance of laboratory testing, the selection of appropriate deep soil mixing techniques, and the evaluation of outcomes to ensure successful soil improvement.E